THE METHODOLOGY FOR THE DEVELOPMENT OF TECHNICAL CREATIVITY OF STUDENTS BASED ON THE STEM APPROACH (USING THE EXAMPLE OF TEACHING PHYSICS). - Ochilova Ozoda Odilovna; Absalyamova Ilmira Ildarovna; Abdullayeva Shoira Isajanovna; Xalilova Nozliya Samadovna (PEDAGOGS, 2024)
Annotation: This article presents a methodology for the development of technical creativity in students using the STEM (Science, Technology, Engineering, and Mathematics) approach. The methodology is illustrated through the example of physics education. By integrating STEM principles into physics teaching, students are encouraged to engage in creative problem-solving, critical thinking, and hands-on experimentation. The study examines existing research on STEM education and presents the results of applying these methodologies in a classroom setting. The article concludes with a discussion of the effectiveness of the approach and offers recommendations for further improvement.